Geometric analysis of loco-regional recurrences in relation to pre-treatment hypoxia in patients with head and neck cancer. (2nd November 2017) - Boeke, Simon; Thorwarth, Daniela; Mönnich, David; Pfannenberg, Christina; Reischl, Gerald; La Fougère, Christian; Nikolaou, Konstantin; Mauz, Paul-Stefan; Paulsen, Frank; Zips, Daniel; Welz, Stefan
Abstract: Introduction: A previous pattern-of-failure study has suggested that up to 50% of the loco-regional failures (LRF) in head and neck squamous cell carcinoma (HNSCC) occur outside the initial hypoxic volume determined by [ 18 F]-fluoromisonidazole-PET ([ 18 F]-FMISO-PET). The aim of the present analysis was to correlate spatial patterns of failure with respect to the pretherapeutic dynamic [ 18 F]-FMISO-PET/CT in HNSCC after radiochemotherapy (RCT). Material and methods: Within a running phase 2 trial using [ 18 F]-FMISO-PET imaging prior to RCT in HNSCC patients ( n  = 54), we have observed so far 11 LRF with a minimum follow-up of 12 months. For nine patients, LRF imaging (CT or [ 18 F]-FDG-PET/CT) for pattern-of-failure analysis was available. Analysis included the static 4-h hypoxic subvolume (VH ) as well as a M-parameter volume (VM ), which is derived from modeling of dynamic PET. Deformable image registration of the CT scan with the recurrent tumor to the pre-treatment [ 18 F]-FMISO-PET/CT and the planning CT was done to quantify the hypoxic subvolumes compared to the recurrent tumor volume. Moreover, a point-of-origin analysis was performed. Results: A total of five local, two regional and two loco-regional recurrences were detected. After deformable image registration of the CT scan with the recurrent tumor to the pre-treatment [ 18 F]-FMISO-PET/CT and the planning CT, a significant overlap of the recurrence volume with [ 18 F]-FMISO-positive subvolumes in the initial gross tumor volume (GTV) was observed. Median overlap of 40.2%, range 9.4–100.0%, for VH and 49.0%, range 4.4–96.4%, for VM was calculated. The point-of-origin analysis showed median distances of 0.0 mm, range 0.0–11.3 mm to VH and 8.6 mm, range 0.0–15.5 mm to VM, respectively. Conclusions: Our data suggest that loco-regional recurrences after RCT originate from the initial GTV (primary tumor and/or lymph node metastases) containing hypoxic subvolumes, which supports the concept of hypoxia imaging-based dose escalation.